Efek Antibakteri Pemberian Aloe Vera Dari Acne Vulgaris - Gusnanto Luthfi Perdana (Yayasan Pendidikan Medika Indonesia, 2023)
Acne vulgaris affects about 85% of people ages 12 to 25 in the United States. In Indonesia, around 95-100% of young men and 83-85% of young women suffer from acne. The prevalence of acne in adult women is about 12% and 3% in adult men. One of the principles of treating acne is to reduce the P. acne population and suppress inflammation. Inflammation in acne can be treated with medications, including erythromycin and clindamycin, and acne treatments. Many sufferers are switching from conventional medicine and looking for alternative treatments. Aloe vera is known to have anthraquinone active compounds (Aloe-emodin) which are structural analogues of tetracyclines and polysaccharides (Acemannan) which can trigger bacterial phagocytosis, thereby contributing to its benefits as an antibacterial. The results of a literature study show that Aloe Vera has an antibacterial effect against acne vulgaris bacteria because it contains saponins and anthroquinones.